Unveiling of active diazotrophs in a flooded rice soil by combination of NanoSIMS and 15N2-DNA-stable isotope probing - Wang, Xiaojie; Bei, Qicheng; Yang, Wei; Zhang, Heng; Hao, Jialong; Qian, Li; Feng, Yucheng; Xie, Zubin (Biology and fertility of soils, 2020)
The biological nitrogen fixation in planted and nonplanted paddy soils was quantified using a chamber-based 15 N 2 -labeling technique, and the active diazotrophs of soil were assessed by 15 N 2 -DNA-stable isotope probing (SIP). In addition, the nanometer scale secondary ion mass spectrometry (NanoSIMS) was applied to analysis the 15 N-enrichment of soil DNA in SIP fractions. 15 N 2 -labeling experiment showed that BNF was 11.33 ± 1.90 kg N ha −1 in the rice-planted soil and 3.55 ± 1.18 kg N ha −1 in the nonplanted soil after 28-day labeling. The biologically fixed 15 N was mainly (> 95%) recovered in the surface layer (0–0.5 cm) in the rice-planted soil. High throughput sequencing of nifH genes extracted from surface soil showed that the presence of rice affected the community composition of diazotrophs. The relative abundance of Nostocales and Stigonematales was significantly higher in rice-planted soil than in nonplanted soil ( P < 0.05). After CsCl gradient ultracentrifugation, NanoSIMS images clearly showed that 15 N was incorporated into soil DNA in the 15 N 2 -labeling SIP gradient fractions. Analyses of nifH genes in 15 N-enriched SIP gradient fractions suggested that Nostocales and Stigonematales were the major contributors to BNF in the rice-soil system. Taken together, these results have highlighted the contributions of cyanobacteria to the BNF in paddy fields and improved our understanding of the close relationship between rice plants and cyanobacteria.